Economic Analysis of Renewable Energy in the Electricity Marketization Framework: A Case Study in Guangdong, China - Liu, Wenfeng; Zhang, Xingping; Wu, Yangyan; Feng, Sida (Frontiers in Energy Research, 2020)
Abstract: Along with China's rapid advancement of electricity market reform, market-oriented policies in promoting renewable energy development and accommodation are foreseeing. Assessing the economics of renewable energy under electricity marketization is an important issue worthy of study. In this paper, we firstly employ merit order method to establish an electricity market clearing model of the electricity trading by modeling 48 hypothetical scenarios. Then we simulate the market clearing prices at 15-minute intervals to discuss the economics of renewable energy in a benchmark feed-in tariff (FIT) scenario and a market-oriented scenario with the historical data of Guangdong, China. Further, the study exams the economic interrelationship between the outputs of wind and solar power in different load scenarios. The results demonstrate that the consumption of renewable energy is greatly improved in the market-oriented situation. However, in this scenario, renewable energy generation is unprofitable and uneconomic compared with in the benchmark FIT scenario. In the high-load scenarios, the changes in wind power output have a negative impact on the economics of solar power, while the mixed effects exist in the low-load scenarios. Based on these findings, conclusions and policy implications are drawn at the end of the paper.